The historical importance of the concept of business ethics and evaluation in terms of employees in human resources - Adıgüzel, Zafer (IGI Global, 2023)
To provide a better and happier society, the framework of certain principles and the history of the concept of ethics aims to direct the people's behaviours constituting that society. The first known philosophers discussed the concept of ethics at that time. The continuation of discussions about ethics to the present day shows that the importance of the image in human life has never changed and has not lost its actuality. In fact, it isn't easy to show a specific and bordered area of business ethics. In this case, it is possible to narrow the definition of business ethics by excluding some important elements or extending it to a wide area that is completely encompassing. In this study, the historical importance of business ethics and human resources are evaluated.
Keywords: Human Resources; Business Ethics; Historical Importance